Effects of State Anxiety and Ego Depletion on Performance Change in Golf Putting: A Hierarchical Linear Model Application. Issue 5 (October 2019) - Shin, Myoungjin; Kim, Yoora; Park, Seungha
This study employed a hierarchical linear model analysis to examine the effects of ego depletion and state anxiety on performance changes in golf putting. We randomly assigned 51 female college students with no previous golf putting experience to either an ego-depletion (experimental) group ( n  = 26) or a non-ego-depletion (control) group ( n  = 25). Putting performance changes over repeated trials displayed a quadratic curve, and both ego depletion and state anxiety exerted negative effects on early, but not late, putting performance. Contrary to previous findings, the interaction effect between ego depletion and state anxiety on performance was nonsignificant.